Sexual behavioral correlates with HSV-2 seroprevalence among pregnant women in Nigeria (2014)
Introduction: The burden of HSV-2 infection, the cause of most cases of genital herpes in Nigeria, varies from region to region; and so are the associated factors. This infection is known to be responsible for several negative pregnancy outcomes. There is currently no documented data on sexual behavioral factors associated with the occurrence of HSV-2 infection or seroprevalence among pregnant women in Nigeria. This study aimed at identifying the sexual behavioral correlates of HSV-2 seroprevalence among pregnant women in Benin City, Nigeria. Methodology: The cross-sectional study design was adopted and the study took place between November 2011 and June 2012. Four hundred and ten consenting ante-natal clinic patients in two major tertiary hospitals in Benin City were consecutively and prospectively included. Data sources were represented by questionnaires, the patient’s case records and laboratory investigations. Each patient’s serum was analyzed for HSV-2 antibody detection. Data analysis was performed using SPSS version 16. Results: Four hundred and ten patients were enrolled with average age 30.6 years. Seroprevalence of HSV-2 antibody was 47.3%. Sexual behavioral factors that were significantly associated with HSV-2 seroprevalence included early exposure to sexual intercourse, number of sex partners, involvement in polygamous marriages, involvement of husband in extra-marital affairs and hormonal contraceptive use. Conclusion: The prevalence of HSV-2 among pregnant women in Benin City is high. Public health campaigns aimed at: delaying onset of sexual activity; encouraging monogamous relationships; and emphasizing that hormonal contraceptives do not protect from STI’s, are recommended.